2-Aminoacetophenone As A Virulent Factor For Pseudomonas Aeruginosa Causing Sever Burn And Wound Infections In Iraq - Al-Araji, M.K.; Ali., S. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Various pathological specimens (180) were collected from patients suffering from pseudomonas aeruginosa infections from different hospitals in Baghdad from January to May 2011; these specimens include (Blood samples,sputum,urine and wound swabs) were tested for pseudomonas aeruginosa producing 2-Aminoacetophenone.Wounds swabs specially taken from burns and post surgical infections producing a higher concentration of 2-Acetophenone material than from other samples were tested for this material and most ofthese were isolated bases on their distinctive grape- like odor of 2-Aminoacetophenone production usually linked with patients whose immune system compromised by disease or trauma, its gains access to these patients tissue through burns, although the grape odor is sometimes difficult to detect in culture media. These methods can be utilized to assay 2-aminoacetophenone (2AA) production in a varies media. Its synthesis occurs relatively early in the growth cycle. It has proved easy and convenient to detect 2-aminoacetophenone (2AA) excretion by Pseudomonas aeruginosa after 24 h of incubation on blood agar plates employing thin layer chromatography of ether extracts of the agar medium.